Homeostatic plasticity in the retina - Fitzpatrick, Michael J.; Kerschensteiner, Daniel (Progress in retinal and eye research, 2023)
Vision begins in the retina, whose intricate neural circuits extract salient features of the environment from the light entering our eyes. Neurodegenerative diseases of the retina (e.g., inherited retinal degenerations, age-related macular degeneration, and glaucoma) impair vision and cause blindness in a growing number of people worldwide. Increasing evidence indicates that homeostatic plasticity (i.e., the drive of a neural system to stabilize its function) can, in principle, preserve retinal function in the face of major perturbations, including neurodegeneration. Here, we review the circumstances and events that trigger homeostatic plasticity in the retina during development, sensory experience, and disease. We discuss the diverse mechanisms that cooperate to compensate and the set points and outcomes that homeostatic retinal plasticity stabilizes. Finally, we summarize the opportunities and challenges for unlocking the therapeutic potential of homeostatic plasticity. Homeostatic plasticity is fundamental to understanding retinal development and function and could be an important tool in the fight to preserve and restore vision.